Piglet production unit: An approach to sustainable community pig farming in Titabor, Assam - Borgohain, Rupam; Chetia, Sanjay Kumar; Hazarika, Dhrubajit; Hazarika, Hemanjali; Kashyap, Dipanjan; Sarma, Akashi; Saikia, Mrinal; Pathak, Kalyan; Choudhury, Kabyasree; Kotoky, Utpal; Phukan, Rumjhum; Mahanta, Sangita; et al. (Indian Farming, 2025)
The ICAR sponsored Farmer FIRST Programme (FFP) implemented by Assam Agricultural University (AAU) intervened in traditional piggery backyard farming through participatory approach in clusters of villages in Jorhat district in Assam. The farmers rarely provided balanced diet or general healthcare for the pigs. However, FFP successfully implemented two scientific interventions to improve pig farming in the area, viz. capacity building on scientific pig farming, and practical trainings on selection of breed, vaccination, nutrition and healthcare. The article discribes the successful scientific intervention in pig farming in Assam from 2016-2024.